Survival and Estimation of Direct Medical Costs of Hospitalized COVID-19 Patients in the Kingdom of Saudi Arabia (Short Title: COVID-19 Survival and Cost in Saudi Arabia) - Anas A. Khan (International Journal of Environmental Research and Public Health, 2020)
Objectives: Assess the survival of hospitalized coronavirus disease 2019 (COVID-19) patients across age groups, sex, use of mechanical ventilators (MVs), nationality, and intensive care unit (ICU) admission in the Kingdom of Saudi Arabia. Methods: Data were retrieved from the Saudi Ministry of Health (MoH) between 1 March and 29 May 2020. Kaplan–Meier (KM) analyses and multiple Cox proportional-hazards regression were conducted to assess the survival of hospitalized COVID-19 patients from hospital admission to discharge (censored) or death. Micro-costing was used to estimate the direct medical costs associated with hospitalization per patient. Results: The number of included patients with complete status (discharge or death) was 1422. The overall 14-day survival was 0.699 (95%CI: 0.652–0.741). Older adults (>70 years) (HR = 5.00, 95%CI = 2.83–8.91), patients on MVs (5.39, 3.83–7.64), non-Saudi patients (1.37, 1.01–1.89), and ICU admission (2.09, 1.49–2.93) were associated with a high risk of mortality. The mean cost per patient (in SAR) for those admitted to the general Medical Ward (GMW) and ICU was 42,704.49 ± 29,811.25 and 79,418.30 ± 55,647.69, respectively. Conclusion: The high hospitalization costs for COVID-19 patients represents is a significant public health challenge. Efficient allocation of healthcare resources cannot be emphasized enough.